Nursing interventions for drug users : qualitative meta-synthesis - Vasconcelos, Selene Cordeiro (2014)
Abstract Objective: To identify the Brazilians nurses’ interventions in the drug users care. Methods: Research on the databases LILACS, PubMed, Scopus, CINHAL, and Cochrane, indexed from 2003 to 2012, using the keywords ‘health education’ and ‘substance-related disorders’. Obtained 8 articles as sample that resulted in a thematic and two sub themes. Results: Demonstrated that Brazilian nurses’ interventions in the drug users care are grounded in health education. Conclusion: Health education actions are relevant to the process of rehabilitation and social reintegration of drug user, can promote improvement in self-care and in the quality of life of this clientele, in addition to strengthening the nursing professional identity in this setting of care.